RESPON PERTUMBUHAN DAN HASIL TANAMAN BAWANG MERAH (Allium ascalonicum L.) AKIBAT PEMBERIAN BOKASHI KOTORAN KAMBING DAN KONSENTRASI PGPR (Plant Growth Promoting Rhizobacteria) - ikbal yunus; Istirochah Pujiwati; Anis Sholihah (AGRONISMA, 2021)
Shallots (Alium ascalonicum L) is one of the most widely cultivated vegetable crops in Indonesia. The yield of shallots is less than optimal because farmers pay less attention to soil fertility. Improvement of planting media on shallots, one of which is by giving goat manure bokashi. A group of beneficial bacteria that can be useful for plant growth processes and increase crop yields are PGPR (Plant Growth Promoting Rhizobacteria). These bacteria can be purified from bamboo roots through fermentation for three days. The bacteria in PGPR include Pseudomonas sp., Bacillus sp., Azobacter sp., and Azospirilum sp. Factorial Randomized Block Design (RAK) with control, which consists of two factors. The first factor is the dose of goat dung bokashi consisting of 3 levels, namely; K1 : 15 ton/ha, K2 : 20 ton/ha, K3 : 25 ton/ha. The second factor is the concentration of PGPR (Plant growth promoting rhizobacteria), consisting of 3 levels; P1 = 10 ml/liter, P2 = 20 ml/liter, P3 = 30 ml/liter. The results showed that in general the growth parameters of the treatment of bokashi dose of goat manure 25 tons/ha combined with PGPR concentration of 30 ml/liter on plant length and number of leaves and on the parameters of tuber weight yield of tons/ha the best treatment for bokashi dose of 20 tons goat manure. /ha combined with a PGPR concentration of 20 ml/liter.